STAD : A Suitable Technique for Increasing Students’ Vocabulary Mastery - Muhammad Ilyas (J-SHMIC : Journal of English for Academic, 2017)
Increasing students’ vocabulary mastery is not an easy way for English teacher in teaching English in the classroom. To realize the difficulties of increasing students’ vocabulary mastery, the English teacher should consider many strategies of teaching. The strategies that are used should be able to make students feel comfortable and enjoy in the classroom and also should be able to encourage and motivate them to learn. One of the strategies is STAD (Student Teams Achievement Divisions). This research focuses on the implementation of STAD to increase students’ vocabulary mastery. The writer would like to find out whether there is a suitable techniqueor not on students’ vocabulary mastery for junior high school students after applying STAD in teaching and learning process.This research is an experimental study in quantitative research. The research involved two equal qualification of sample groups, they are an experimental group and control group. The instrument that used in this research is vocabulary test.Pre-test were given for both groups, after applying STAD in treatment for experimental group, the pos-test was administered by the two groups, experimental group and control group. The writer found that the mean score of experimental group is 52.59 in pre-test and became 71.66 in post-test and control group is 51.52 in pre-test and became 55.81 in post-test. From the result of mean score from each groups, it can be seen that there is significant improvement from experimental group.Consequently, the useof STAD is more effective to increase vocabulary mastery for junior high school students. And the evidence indicates that teaching English vocabulary by using STAD has significant positive effectand become a suitable technique for increasing students’ vocabulary mastery.